Labor shortages and wage growth - Erik Frohm (Sveriges Riksbank, 2020)
This paper presents a novel measure of labor market conditions based on micro data from a large business survey in Sweden. The indicator, relative labor shortages (RLS), is the ratio of respondents' quantitative assessment of labor shortages and current employment. Contrary to other surveybased measures of labor market conditions and the vacancy-unemployment ratio, RLS remained relatively subdued during the 2013-2018 recovery from the Great Recession. As the indicator is highly correlated with annual wage growth at the establishment-level, its slow recovery can help explain why wage growth in Sweden has been sluggish since the Great Recession.
Keywords: E31; E60; J31; J23; C80; 330; Wage inflation; labor shortages; survey data